Enhancements for wideband CDMA systems - Vo, Viet Linh (2014)
This report is a summary of the experience and knowledge the student has gained and the project he has done throughout his final year at the School of Electrical and Electronic Engineering, Nanyang Technological University. In this report, background information of digital modulation, noise, fading, matched filter and spread spectrum communication system is first provided. After that, the student discusses his project in detail by explaining his simulation model in different scenarios as well as results accordingly. Serial interference cancellation (SIC) and parallel interference cancellation (PIC) algorithms are then discussed later as the main enhancements to integrate into the existing system. Finally, the student gives a conclusion to sum up the result of his project, observations made by him and what he has learned from this meaningful project.